Epidural Hematoma Volume and Glasgow Coma Scale Score: A Cross-Sectional Analysis of Head Injury Patient - Stefanus Satria Adi Dharma; Erie Bambang Prijono Setyabudi Andar (Bioscientia Medicina : Journal of Biomedicine and Translational Research, 2025)
Background: Epidural hematoma (EDH) is a common neurosurgical emergency with potentially life-threatening consequences. The Glasgow Coma Scale (GCS) is a widely used tool for assessing the severity of head injuries, but its correlation with EDH volume remains unclear. This study aimed to investigate the relationship between EDH volume and GCS score in head injury patients. Methods: A retrospective cross-sectional analysis was conducted on 63 patients with head injuries and EDH admitted to a tertiary care hospital between 2021 and 2023. EDH volume was measured using computed tomography (CT) scans, and GCS scores were recorded upon admission. Statistical analysis was performed to assess the correlation between EDH volume and GCS score. Results: The mean EDH volume was 30.5 ml (SD = 22.5), and the mean GCS score was 11.2 (SD = 3.8). A significant negative correlation was found between EDH volume and GCS score (r = -0.437, p < 0.001), indicating that larger EDH volumes were associated with lower GCS scores. Conclusion: EDH volume is significantly correlated with GCS score in head injury patients. This finding underscores the importance of prompt diagnosis and surgical intervention for EDH, especially in patients with large hematomas and low GCS scores.